GstLAL: A software framework for gravitational wave discovery - Cannon, Kipp; Caudill, Sarah; Chan, Chiwai; Cousins, Bryce; Creighton, Jolien D.E.; Ewing, Becca; Fong, Heather; Godwin, Patrick; Hanna, Chad; Hooper, Shaun; Huxford, Rachael; Magee, Ryan; et al. (SoftwareX, 2021)
The GstLAL library, derived from Gstreamer and the LIGO Algorithm Library, supports a stream-based approach to gravitational-wave data processing. Although GstLAL was primarily designed to search for gravitational-wave signatures of merging black holes and neutron stars, it has also contributed to other gravitational-wave searches, data calibration, and detector-characterization efforts. GstLAL has played an integral role in all of the LIGO-Virgo collaboration detections, and its low-latency configuration has enabled rapid electromagnetic follow-up for dozens of compact binary candidates.